The Fourfold Cosmological Structure of Dayak Culture: A Structural Anthropological Analysis - Imam Qalyubi; Apni Ranti; Misrita Misrita; Huili Li; Irish Mae F. Dalona (International Journal of Post Axial: Futuristic Teaching and Learning, 2026)
The cosmological worldview of the Dayak communities has long been reflected in various cultural practices, yet studies examining the underlying symbolic structure that integrates these practices remain limited. This study aims to analyze the fourfold cosmological structure (serba empat) as the deep symbolic system underlying the culture of the Dayak communities along the Barito River, Central Kalimantan. Employing a qualitative ethnographic approach, the study utilizes field observations, in-depth interviews, documentation, and textual analysis of customary traditions. Data were analyzed using Claude Lévi-Strauss's structural anthropology through the processes of data reduction, categorization, structural interpretation, and verification. The findings reveal that the serba empat cosmology constitutes the underlying cultural structure that organizes ritual practices, traditional architecture, settlement patterns, agricultural activities, healing traditions, oral narratives, and customary institutions. Rather than functioning merely as a numerical concept or ritual convention, the fourfold principle serves as a symbolic framework that integrates relationships among humans, nature, ancestors, and the supernatural. The study further demonstrates that the continuity of Dayak culture is maintained through the persistence of this deep symbolic structure despite religious and social transformations. Theoretically, the findings extend Lévi-Strauss's structural anthropology beyond myth analysis by demonstrating that indigenous cosmology functions as an organizing framework connecting symbolic systems, indigenous knowledge, and cultural practices. This study contributes to the broader understanding of indigenous cosmology and provides a structural perspective for future comparative research on the cultural systems of indigenous societies in Southeast Asia.